IMPLEMENTATION OF JOYFUL LEARNING STRATEGY USING FLASH CARD MEDIA IN BASIC MATHEMATICS LEARNING - Khurin In Ratnasari; Asnawan Asnawan; Mohammad Dasuki; M. Bustanul Ulum; Nanang Budianto; Khusnul Khotimah (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to describe the implementation of the Joyful Learning strategy using flash card media in mathematics learning and its impact on students’ motivation and understanding. This type of research is descriptive qualitative. The subjects of the study were fourth grade students of MI 2 Jombang Jember. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the Joyful Learning strategy with flash card media can create a pleasant learning atmosphere, increase active student participation, and facilitate understanding of mathematical concepts. These findings support the importance of innovation in learning strategies and media to improve the quality of the teaching and learning process, especially at the elementary education level.